Reported barriers to healthcare access and service disruptions caused by COVID-19 in Burkina Faso, Ethiopia, and Nigeria: a telephone survey - Assefa, Nega; Sié, Ali; Wang, Dongqing; Korte, Michelle L.; Hemler, Elena C.; Abdullahi, Yasir Y.; Lankoande, Bruno; Millogo, Ourohiré; Chukwu, Angela; Workneh, Firehiwot; Kanki, Phyllis; Bärnighausen, Till; et al. (The American journal of tropical medicine and hygiene, 2021)
ABSTRACT. The coronavirus disease 2019 (COVID-19) pandemic may have short-term and long-term impacts on health services across sub-Saharan African countries. A telephone survey in Burkina Faso, Ethiopia, and Nigeria was conducted to assess the effects of the pandemic on healthcare services from the perspectives of healthcare providers (HCPs) and community members. A total of 900 HCPs (300 from each country) and 1,797 adult community members (approximately 600 from each country) participated in the study. Adjusted risk ratios (ARRs) and 95% confidence intervals (CIs) were computed using modified Poisson regression. According to the HCPs, more than half (56%) of essential health services were affected. Child health services and HIV/surgical/other services had a slightly higher percentage of interruption (33%) compared with maternal health services (31%). A total of 21.8%, 19.3%, and 7.7% of the community members reported that their family members and themselves had difficulty accessing childcare services, maternal health, and other health services, respectively. Nurses had a lower risk of reporting high service interruptions than physicians (ARR, 0.85; 95% CI, 0.56-0.95). HCPs at private facilities (ARR, 0.71; 95% CI, 0.59-0.84) had a lower risk of reporting high service interruptions than those at governmental facilities. Health services in Nigeria were more likely to be interrupted than those in Burkina Faso (ARR, 1.38; 95% CI, 1.19-1.59). Health authorities should work with multiple stakeholders to ensure routine health services and identify novel and adaptive approaches to recover referral services, medical care, maternal and child health, family planning, immunization and health promotion, and prevention during the COVID-19 era.
Gesehen am 05.05.2022